PPARG Epigenetic Deregulation and Its Role in Colorectal Tumorigenesis - Lina Sabatino; Alessandra Fucci; Massimo Pancione; Vittorio Colantuoni (PPAR Research)
Peroxisome proliferator-activated receptor gamma (PPARγ) plays critical roles in lipid storage, glucose metabolism, energy homeostasis, adipocyte differentiation, inflammation, and cancer. Its function in colon carcinogenesis has largely been debated; accumulating evidence, however, supports a role as tumor suppressor through modulation of crucial pathways in cell differentiation, apoptosis, and metastatic dissemination. Epigenetics adds a further layer of complexity to gene regulation in several biological processes. In cancer, the relationship with epigenetic modifications has provided important insights into the underlying molecular mechanisms. These studies have highlighted how epigenetic modifications influence PPARG gene expression in colorectal tumorigenesis. In this paper, we take a comprehensive look at the current understanding of the relationship between PPARγ and cancer development. The role that epigenetic mechanisms play is also addressed disclosing novel crosstalks between PPARG signaling and the epigenetic machinery and suggesting how this dysregulation may contribute to colon cancer development.